Immunotherapy Resistance Mechanisms in Renal Cell Cancer - Kaminska, Katarzyna; Wcislo, Gabriel; M. Czarnecka, Anna; Chouaib, Salem; Szczylik, Cezary (Current Signal Transduction Therapy, 2013)
The successful treatment of renal cancer remains a therapeutic challenge. Clear Cell Renal Cell Carcinoma (ccRCC) is resistant to conventional radio and chemotherapy, but complete response has been observed after immunotherapy with high-dose interleukin-2 (IL-2) and interferon (IFN)-α. Nevertheless, immunotherapy strategies have shown response rates in the range of 5 to 10%. For the past 20 years, the mechanisms of treatment resistance have been studied, and immune escape of tumours in cancer development and spread has been a broadly investigated phenomenon. Multiple studies have revealed that genomic abnormalities of ccRCC promote the loss of major histocompatibility complex (MHC) molecules on the renal cancer cell surface, resulting in immune response resistance. Studies have shown that IFN-α-induced signalling pathways are deregulated in ccRCC cells and promote immune escape. Polymorphisms of multiple genes, including STAT3, have been shown to trigger immune-response deregulation. Investigation and understanding of the mechanisms of renal cell cancer immunotherapy resistance are extremely important for the design of rational combinatorial approaches and other novel therapies in the future. This mini-review focuses on immunotherapy resistance mechanisms in ccRCC.
Keywords: IL-2 induced immunotherapy